2016
DOI: 10.3390/f7110266
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of Ectomycorrhizal Seedlings of Quercus glauca, Quercus salicina, Quercus myrsinaefolia, and Castanopsis cuspidata Planted in Calcareous Soil

Abstract: Abstract:To verify the acclimation capacity of evergreen Fagaceae species on calcareous soil, we compared ecophysiological traits between Quercus glauca Thunb., Q. salicina Blume, Q. myrsinaefolia Blume, and Castanopsis cuspidata (Thunb.) Schottky as typical woody species from southwestern Japan. We also examined the inoculation effects of the ectomycorrhizal (ECM) fungi Astraeus hygrometricus and Scleroderma citrinum, and planted seedlings in calcareous soil collected from a limestone quarry. We measured grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…Our findings support that connectivity between the LGM and currently suitable habitats is a key factor in range filling (Figure 4), which is in line with previous findings that past connectivity can influence current species distributions (Graham et al, 2010;Pabijan et al, 2015). Other than connectivity, another likely mechanism corresponds to our finding that the % LGM ice sheets is negatively associated with range filling, which could be caused by the lagged accumulation of suitable soil substrates (Giesecke et al, 2017;Hutchinson, 1918;Pennington, 1986) and lagged development of mutualisms, especially ectomycorrhizal association essential for oaks (Kayama & Yamanaka, 2016;Southworth et al, 2009). Our support for both mechanisms hints that studies of plant range shifts under climate warming should consider both the connectivity of suitable habitat and the lagged development of soil and soil microbes.…”
Section: Support For and Implications Of The Four Hypothesessupporting
confidence: 92%
“…Our findings support that connectivity between the LGM and currently suitable habitats is a key factor in range filling (Figure 4), which is in line with previous findings that past connectivity can influence current species distributions (Graham et al, 2010;Pabijan et al, 2015). Other than connectivity, another likely mechanism corresponds to our finding that the % LGM ice sheets is negatively associated with range filling, which could be caused by the lagged accumulation of suitable soil substrates (Giesecke et al, 2017;Hutchinson, 1918;Pennington, 1986) and lagged development of mutualisms, especially ectomycorrhizal association essential for oaks (Kayama & Yamanaka, 2016;Southworth et al, 2009). Our support for both mechanisms hints that studies of plant range shifts under climate warming should consider both the connectivity of suitable habitat and the lagged development of soil and soil microbes.…”
Section: Support For and Implications Of The Four Hypothesessupporting
confidence: 92%
“…Drought stress significantly hinders nutrient uptake and assimilation, thereby affecting plant growth [ 7 , 8 ]. In general, AMF colonization can improve plant nutritional status by increasing nutrient acquisition in plants [ 82 , 83 ] and also in nutrient deficient soils [ 83 , 84 ]. Accordingly, different studies have confirmed the contribution of AMF colonization in overcoming drought stress by improving plant nutrition, which could be considered as an important drought tolerance mechanism [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distantly related oak species tend to share a proportion of their ECM symbionts (Desai et al, 2016) despite significant differentiation in ECM communities among distantly related oak hosts (Cavender-Bares et al, 2009a). ECM symbionts enhance growth of oak seedlings and likely allow them to persist in nutrient-poor soils by mobilization of various nitrogen and phosphorus forms from organic soil layers (Berman & Bledsoe, 1998;Kayama & Yamanaka, 2016). There is evidence that ECM mutualists enhance the ability of oaks to colonize new niches (Yguel et al, 2014).…”
Section: Reviewmentioning
confidence: 99%